The role of 6‐acetylmorphine in heroin‐induced reward and locomotor sensitization in mice. (20th February 2019) - Kvello, Anne Marte Sjursen; Andersen, Jannike Mørch; Boix, Fernando; Mørland, Jørg; Bogen, Inger Lise
Abstract: We have previously demonstrated that heroin's first metabolite, 6‐acetylmorphine (6‐AM), is an important mediator of heroin's acute effects. However, the significance of 6‐AM to the rewarding properties of heroin still remains unknown. The present study therefore aimed to examine the contribution of 6‐AM to heroin‐induced reward and locomotor sensitization. Mice were tested for conditioned place preference (CPP) induced by equimolar doses of heroin or 6‐AM (1.25‐5 μmol/kg). Psychomotor activity was recorded during the CPP conditioning sessions for assessment of drug‐induced locomotor sensitization. The contribution of 6‐AM to heroin reward and locomotor sensitization was further examined by pretreating mice with a 6‐AM specific antibody (anti–6‐AM mAb) 24 hours prior to the CPP procedure. Both heroin and 6‐AM induced CPP in mice, but heroin generated twice as high CPP scores compared with 6‐AM. Locomotor sensitization was expressed after repeated exposure to 2.5 and 5 μmol/kg heroin or 6‐AM, but not after 1.25 μmol/kg, and we found no correlation between the expression of CPP and the magnitude of locomotor sensitization for either opioid. Pretreatment with anti–6‐AM mAb suppressed both heroin‐induced and 6‐AM–induced CPP and locomotor sensitization. These findings provide evidence that 6‐AM is essential for the rewarding and sensitizing properties of heroin; however, heroin caused stronger reward compared with 6‐AM. This may be explained by the higher lipophilicity of heroin, providing more efficient drug transfer to the brain, ensuring rapid increase in the brain 6‐AM concentration. Abstract : The present study examined the contribution of heroin's first metabolite, 6‐acetylmorphine (6‐AM), to the rewarding properties of heroin. Both heroin and 6‐AM induced conditioned place preference (CPP) and locomotor sensitization in mice, but heroin generated twice as high CPP scores compared with 6‐AM. Our findings provide evidence that 6‐AM is essential for heroin‐induced reward; however, heroin caused stronger reward compared with 6‐AM, possibly explained by the higher lipophilicity of heroin providing a more efficient drug transfer to the brain.